Association of neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, and De Ritis ratio with mortality in renal cell carcinoma: A multicenter analysis - Keiner, Cathrine; Meagher, Margaret; Patil, Dattatraya; Saito, Kazutaka; Walia, Arman; Liu, Franklin; Dutt, Raksha; Miller, Nathan; Dhanji, Sohail; Saidian, Ava; Wan, Fang; Yasuda, Yosuke; et al. (Frontiers in Oncology, 2022)
Background: Renal Cell Carcinoma (RCC) is a metabolically driven disease and several markers of inflammation have been associated with oncologic outcomes. Predictive markers associated with mortality are not well-defined. We sought to investigate the association of preoperative neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and De Ritis Ratio with mortality in RCC.¶ Methods: Multi-center retrospective analysis of patients undergoing surgery for RCC. Primary outcome of interest was all-cause mortality. Secondary outcomes were non-cancer and cancer-specific mortality. Elevated NLR was defined as ≥2.27, elevated PLR as ≥165, and elevated Di Ritis Ratio as ≥ 2.72. Primary and secondary outcomes were compared between high versus low NLR, PLR, and De Ritis ratio using Kaplan-Meier analysis (KMA). Multivariable cox regression analysis (MVA) was conducted to elucidate risk factors for primary and secondary outcomes controlling for various parameters. ¶ Results: 2928 patients were analyzed (956 patients had elevated NLR; 531 patients had elevated PLR and 935 patients had elevated De Ritis). Elevated NLR was a significant predictor of all-cause mortality (HR 1.46, p=0.003) and non-cancer mortality (HR 2.13, p<0.001) in multivariable models. Elevated PLR was a significant predictor of cancer-specific mortality with MVA (HR 1.46, p=0.030). KMA revealed a significant difference in 5-year overall survival (OS) (48% vs. 68%, p<0.001), non-cancer survival (NCS) (69% vs. 87%, p<0.001), and cancer-specific survival (CSS) (60% vs. 73%, p<0.001) for elevated versus non-elevated NLR. For PLR, there was a difference in 5-year OS (51% vs. 61%, p<0.001) and CSS (60% vs. 73%, p<0.001) with KMA. De Ritis ratio was not significantly associated with the studied outcomes on KMA or MVA. ¶ Conclusions: Elevated NLR and PLR were associated with different outcomes in patients surgically treated for RCC. Elevated De Ritis ratio was not predictive of the outcomes studied. These differences may be useful in refining risk stratification with respect to cancer-related and non-cancer mortality in RCC patients and deserve further investigation.